Morbidity pattern and mortality of neonates admitted in a tertiary level teaching hospital in Bangladesh - Islam, MN; Siddika, M; Hossain, MA; Bhuiyan, MK; Ali, MA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):159-62. The abstract of this article is available on the PubMed website